Analysis of the Effect of Sloshing on Damage Stability after the Addition of LNG Tanks - Agoes Santoso; Achmad Baidowi; Mardisuin Siahaan (Institut Teknologi Sepuluh Nopember, 2020)
The Damage Stability, better known as leaky ship stability, is a condition where the vessel has a leak in the ship's compartment so that the stability condition of the ship is disrupted. This study is a study of the effects caused by sloshing on the stability of the ship. The method used to calculate damage stability is the lost buoyancy method. This method assumes a condition where when the vessel has a leak, the vessel buoyancy will decrease. This happens because the empty space in the vessel will be filled with water, so it is no longer the part that contributes to the buoyancy so that the ship will increase and can result in sinkage. According to the calculation of SOLAS (Safety of Life at Sea) Consolidated Edition 2014 Chapter II-1 Part B-1. There are two indexes compared, namely index Required index R = 0.77172, which depends on the length of the lining and Attained subdivision index A = 0.83736. The pi factor shows a maximum of 5 leak zones that can be overcome by the ship to remain stable. By comparing the index value of A> R, it can be seen that this ship has fulfilled the SOLAS requirements.